COTTON FARMING AND COTTON GROWING TECHNOLOGIES IN UZBEKISTAN - Ochilov Jahongir Boymurodovich (American Journals, 2022)
In this article, opinions were expressed about the cotton industry and its cultivation technologies in our country.
Keywords: cotton, yield, cotton, variety, pest, moisture, plow